PENGARUH MOTIVASI, KEDISIPLINAN DAN METODE BELAJAR TERHADAP PRESTASI ANAK DI TK KUNTUM BATAM LITTLE ANGEL - Sihaloho, Asner; Tamba, Imelda; Nuraeni, Brigida Endah; Siki, Elfrida Anunu (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2024)
This research aims to determine the influence of motivation, discipline and learning methods on children's achievement at Kuntum Batam Little Angel Kindergarten. This research method uses quantitative research methods. The population in this research is the parents of students at Kuntum Batam Little Angel Kindergarten with a total of 45 people. The sampling technique in this research used saturated samples, so the number of samples used was 45 respondents. The data collection technique used in this research was literature study and distributing questionnaires. The results of the research with a significance level of 5% show that the motivation variable t value is calculated at 0.082 with a significance level of 0.935> 0.05, so there is a positive and significant influence of motivation on children's achievement. The calculated t value of the discipline variable is 3.266 with a significance level of 0.002<0.05, so there is a positive and significant influence of discipline on children's achievement. The learning method variable has a calculated t value of 1.271 with a significance level of 0.211> 0.05, so there is a positive and significant influence of learning methods on children's achievement. From the F test it is known that the calculated F value for motivation, discipline and learning methods is 79.463 with a significance level of 0.000. A significance value smaller than α = 0.05 shows that motivation, discipline and learning methods simultaneously influence children's achievement at Kuntum Batam Little Angel Kindergarten.